The effectiveness of multifactor leadership of headmaster perceived by teachers and parents / Mohamad Zain Bujang - Bujang, Mohamad Zain (2012)
The purpose of this study is to identify the effectiveness of multifactor leaderships of headmaster from the view of teachers and parents. The study acquired a quantitative approach using survey questionnaires and documents analysis to collect data. The research samples were 200 teachers and 200 parents from all the five 5 primary schools in the North Kuching city, Sarawak who worked directly and indirectly with the headmaster. The findings show that there is no significant differences between perception of male teachers and female teachers towards their headmaster’s leadership effectiveness, but it is noted that both male and female teachers seemed to share same perceptions that an effective and strong headmaster should possesses “inspirational motivation” and “idealized behavior” (Mean = 3.0). There is significant differences between teachers’ and parents’ perceptions towards headmaster’s leadership effectiveness in term of “individual consideration’’ (t = 4.014; p<.01) and “laissez-faire” (t=2.929; p<.05). In regard to ethnicity, the Malay ethnic perceived “idealized behavior” (F=6.086; p<.001) and “inspirational motivation” (F=5.168; p<.05) to be the most effective traits of headmaster’s leadership, whilst the Chinese ethnic perceived “intellectual stimulation” (F=3.661; p<.05) and “individual consideration'’ (F=3.256; p<.05) to be the most effective traits of headmaster’s leadership. The findings also reveal that “Inspirational motivation ” has highest significant correlation with “intellectual stimulation” (r=.795; p<.01); “idealized behavior” (r=.704; p<.01); and “satisfaction" (r=.702; p<.01), respectively. All of those are traits or characteristics of transformational leadership. Effective and successful leadership is not the result of simply obtaining a position, but rather possessing the knowledge and understanding of effective leadership traits and leadership skills along with the personal adaptability of those traits and the ability to effectively implement those skills. As a conclusion, the findings are significantly important for interested parties in the field of school leadership and some suggestions are also raised for further researches to better understanding of the effectiveness of multifactor leadership in schools.